Relationship Between Nurses' Social Health and Quality of Life - Marhamat Farahaninia; Parvin Ehyaei; Zahra Ahmadi; Hamid Haghani (Iran University of Medical Sciences, 2019)
Background: Social health is a crucial health aspect. Nurses are among the most important healthcare providers, and their quality of life bares great importance for providing quality healthcare. Therefore, this study aimed at determining the relationship between social health and quality of life nurses working in hospitals affiliated to Iran University of Medical Sciences (IUMS). Methods: In this descriptive correlational study, 227 nurses were selected by cluster random sampling method from five hospitals affiliated to IUMS. The research instruments consisted of demographic information form, Keys Social Health questionnaire, and the 36-Item Short-Form Health Survey (SF-36). The obtained data were analyzed by descriptive tests (frequency, Mean±SD), as well as  Analysis of Variance (ANOVA), Independent Samples t-test, Pearson's correlation coefficient, and multiple linear regressions in SPSS. Results: The Mean±SD score of nurses' social health was 67.22±8.96 with the lowest score in social solidarity (9.16±2.34) and the highest score in social participation (18.58±2.52). The Mean±SD score of nurses' quality of life was 64.62±18.6. The lowest score related to energy and fatigue (59.09±18.49), and the highest one was associated with the physical function (79.55±21.83). The collected results suggested a significant association between the quality of life and all aspects of social health (P<0.05). There was no significant relationship between social health and the demographic characteristics of the studied nurses (P>0.05). There was a significant relationship between the quality of life and age (P=0.046), work experience (P=0.03), marital status (P=0.024), and income (P=0.041).  Conclusion: The studied nurses' quality of life was associated with their social health; thus, it is suggested that the relevant managers and policymakers take serious steps to improve this group's quality of life and social health if interested in the quality of patient care.